2016
DOI: 10.1021/acs.jpca.6b01855
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the O-Atom Exchange Reaction 16O(3P) + 18O18O(3Σg) → 16O18O(3Σg) + 18O(3P) at Hyperthermal Energies

Abstract: The O-atom exchange reaction, 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Previous studies (e.g., Dawes et al , and Powell et al) only focused on the set of singlet O 3 PESs, which has only a small statistical weight (1/9), or on the surfaces relevant to ozone photodissociation (e.g., Grebenshchikov et al). Recently, in their comparison to further validate Varga et al’s PESs, Geistfeld and Schwartzentruber found good agreement between their QCT calculations and the experimental data by Lahankar et al…”
Section: Introductionmentioning
confidence: 77%
“…Previous studies (e.g., Dawes et al , and Powell et al) only focused on the set of singlet O 3 PESs, which has only a small statistical weight (1/9), or on the surfaces relevant to ozone photodissociation (e.g., Grebenshchikov et al). Recently, in their comparison to further validate Varga et al’s PESs, Geistfeld and Schwartzentruber found good agreement between their QCT calculations and the experimental data by Lahankar et al…”
Section: Introductionmentioning
confidence: 77%
“…Opacity functions were determined by running 50 000 trajectories at each impact parameter The statistical errors of the quantities obtained with the Monte Carlo QCT method were calculated using the standard prescription, , and in most cases are as small as the size of symbols shown in the plots. The calculations were performed using an extensively modified version , of the VENUS code . The potential energy surface developed earlier, , referred to as CGSL PES was used for the simulations of reaction , while the trajectory calculations for reaction were performed using the PES of de Oliveira et al…”
Section: Methodsmentioning
confidence: 99%
“…QCT calculations have been performed according to the standard methodology, with the specific features described in refs . Similar to refs , we used the PES developed by Babikov et al for the electronic ground state.…”
Section: Methodsmentioning
confidence: 99%
“…According to the calculated lifetime distributions, in the majority of collisions, the complex lives for only a few vibrational periods, which cannot be expected to be enough for efficient intramolecular energy scrambling and can be the origin of the inadequacy of the statistical theory. Another set of crossed-beam experiments has been performed at a much higher, hyperthermal collision energy (86 kcal mol −1 ) 20 and produced rather interesting results. In these experiments, the time-of-flight and the angular distributions of not only the products of isotope exchange (reactive) but also those of the inelastic collisions have been determined and compared with those obtained in QCT calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation